A novel method for measuring learning opportunities provided by parents to young children with autism spectrum disorder. (August 2019) - Davlantis, Katherine S; Estes, Annette; Dawson, Geraldine; Rogers, Sally J
The aim of this study was to develop a measurement approach to assess the learning opportunities provided by parents to their young children with autism spectrum disorder during a free play task and to examine the relationship between learning opportunities and child performance on measures of cognition, autism spectrum disorder symptoms, and language. Participants were 91 children with autism spectrum disorder ages 12–24 months and their parents. Ordinary least squares regression was used. Results showed that children whose parents provided more learning opportunities had significantly higher cognitive scores and significantly higher vocabulary comprehension and production. The psychometric properties of the measurement approach were investigated and results indicated that it may be psychometrically sound.